Putting foucault to work on the environment: Exploring pro-environmental behaviour change as a form of discipline - Tom Hargreaves (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
Calls for pro-environmental behaviour change among individuals have become commonplace within the ecological modernist framework. To date, research on pro-environmental behaviour has tended to emphasise either the more or less rational decision-making processes undertaken by individuals, or the ways in which broader social discourses and practices enable or constrain pro-environmental action. As far as politics enters into these discussions, it is normally with respect to how responsibility for addressing environmental problems should be allocated between individuals, governments or businesses. By contrast, this paper employs Foucaults understanding of disciplinary power to interrogate the micro-political processes of social control at work inside behaviour change interventions through which action by individuals comes to be seen as most appropriate solution to global environmental issues. Drawing on an ethnographic case study of a behaviour change intervention called Environment Champions run in the head offices of a British construction company called Burnetts, it reveals the centrality of various subtle techniques of surveillance, normalisation and discipline to behaviour change processes. In so doing, it conceives of behaviour change less as a process of encouraging individuals voluntarily to choose pro-environmental behaviour, and more as one of making up environmental subjects for whom such acts are appropriate.
Keywords: 330; Pro-environmental behaviour change; sustainable consumption; Foucault; discipline; ethnography; Verhalten; Umweltbewusstsein; Ethnologie; Nachhaltigkeit